Radio listening clubs in Malawi and Zambia - Fackson Banda (Communicare)
This paper, based upon a field research project commissioned by the Panos Institute Southern Africa, investigates the communicative efficacy of the radio listening clubs project implemented by the Institute in Malawi and Zambia. The investigation takes the form of a ‘second-order interpretation’ of the key findings of the field research. The findings are analysed in terms of the participatory communication model of development communication. The paper argues that the clubs live up to some of the ideal-typical attributes of participatory communication. This is evident in the following areas: (i) a propensity for social mobilisation; (ii) acquisition of skills and knowledge; (iii) communally induced motivation to listen to the radio; (iv) the possibility of interpersonal influence within groups; (v) the benefit of being ‘organised’ structures; (vi) the ‘massive’ reach of the clubs; and (vii) the dialogic interchanges between the rural-based groups and the urban-based policymaking elites.